Tingkat Kepuasan Masyarakat dalam Pelayanan Kesehatan di Provinsi Maluku Utara: Studi Kasus RSUD. Chasan Boesoiri - Muammil Sun’an; Marwan Man Soleman; Nurlaila Nurlaila (Studi Ilmu Manajemen dan Organisasi, 2024)
Purpose: This research aims to identify and analyze the quality of health services in North Maluku Province, the level of community satisfaction with these services, and the role of the government in encouraging efforts to improve health services.Methodology: The data was analyzed using descriptive and qualitative statistical analysis frameworks. Descriptive statistics analyze variables presented in frequency distributions, both in absolute numbers and percentages.Results: The research results show that there are still various aspects of government health services that require improvement, such as administrative problems, medical personnel, equipment, and supporting facilities. Public complaints include medical costs not commensurate with services, a less clean and comfortable environment, and service delays due to a lack of medical personnel. Conclusions: Public satisfaction with government-provided health services still faces various shortcomings that need to be continuously improved, including administrative issues, workforce, equipment, and other supporting facilities. Therefore, the government needs to allocate a budget for health subsidies.Limitations: Factors such as demographic differences and economic conditions have not been explored, nor have service provider perspectives that could provide insight into internal constraints. This limitation must be considered in further research with more diverse methods and data.Contribution: These findings can be a basis for policymakers in designing strategies for improving health services, including more appropriate budget allocation and improved procedures. This research also opens opportunities to explore demographic factors and service provider perspectives to enrich understanding of challenges and solutions in the health system.